2017
DOI: 10.1186/s11689-017-9184-y
|View full text |Cite
|
Sign up to set email alerts
|

Acamprosate in a mouse model of fragile X syndrome: modulation of spontaneous cortical activity, ERK1/2 activation, locomotor behavior, and anxiety

Abstract: BackgroundFragile X Syndrome (FXS) occurs as a result of a silenced fragile X mental retardation 1 gene (FMR1) and subsequent loss of fragile X mental retardation protein (FMRP) expression. Loss of FMRP alters excitatory/inhibitory signaling balance, leading to increased neuronal hyperexcitability and altered behavior. Acamprosate (the calcium salt of N-acetylhomotaurinate), a drug FDA-approved for relapse prevention in the treatment of alcohol dependence in adults, is a novel agent with multiple mechanisms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 119 publications
5
18
0
1
Order By: Relevance
“…Administration of GABA B agonists, such as baclofen or arbaclofen, corrects exacerbated protein synthesis and multiple phenotypes in Fmr1 -KO mice 3739 . Acamprosate, which activates GABA B and GABA A receptors 40 , also ameliorates several phenotypes in Fmr1 -KO mice 41 . GABA A family receptors and enzymes required for the production of GABA are expressed at reduced levels in Fmr1 -KO mice compared with wild-type mice 42 , and this phenotype can be rescued by introducing a yeast artificial chromosome (YAC) containing the ‘healthy’ human FMR1 genomic region into Fmr1 -KO mice 43 .…”
Section: Molecular Pathophysiology Of Fxsmentioning
confidence: 97%
“…Administration of GABA B agonists, such as baclofen or arbaclofen, corrects exacerbated protein synthesis and multiple phenotypes in Fmr1 -KO mice 3739 . Acamprosate, which activates GABA B and GABA A receptors 40 , also ameliorates several phenotypes in Fmr1 -KO mice 41 . GABA A family receptors and enzymes required for the production of GABA are expressed at reduced levels in Fmr1 -KO mice compared with wild-type mice 42 , and this phenotype can be rescued by introducing a yeast artificial chromosome (YAC) containing the ‘healthy’ human FMR1 genomic region into Fmr1 -KO mice 43 .…”
Section: Molecular Pathophysiology Of Fxsmentioning
confidence: 97%
“…Articles Articles Musumeci et al, 2000Westmark et al, 2011Gholizadeh et al, 2014Chen and Toth, 2001Goebel-Goody et al, 2012Gross et al, 2015aYan et al, 2004Henderson et al, 2012Gross et al, 2015bQin et al, 2005Heulens et al, 2012Zhao et al, 2015Yan et al, 2005Michalon et al, 2012Guo et al, 2016Dölen et al, 2007Ronesi et al, 2012Sawicka et al, 2016Musumeci et al, 2007Thomas et al, 2012Gantois et al, 2017Min et al, 2009Veeraragavan et al, 2012Saré et al, 2018Pacey et al, 2009Wang et al, 2012Schaefer et al, 2017Westmark et al, 2009Busquets-Garcia et al, 2013Sethna et al, 2017Zang et al, 2009Curia et al, 2013Stoppel et al, 2017Osterweil et al, 2010Dansie et al, 2013Thomson et al, 2017Zhong et al, 2010Dolan et al, 2013Chatterjee et al, 2018Pacey et al, 2011Osterweil et al, 2013Gross et al, 2019Thomas et al, 2011Udagawa et al, 2013…”
Section: Articlesmentioning
confidence: 99%
“…Downstream of CYFIP1, the mTor target ribosomal protein s6 is hyperphosphorylated by p90-ribosomal S6 kinase (RSK), downstream of both extracellular signal-regulated kinase (ERK) and phosphatidylinositide 3 kinase (PI3K) signaling elevated in FXS model mice [46,47]. A recent study found Acamprosate decreases elevated ERK signaling to attenuate functional and behavioral defects [48]. Finally, in mice FMRP also binds adenylyl cyclase type 1 (ADCY1) mRNA to suppress translation, and elevated ADCY1 expression in the FXS condition also activates the above pathway to promote postsynaptic spine overgrowth (Table 2) [47].…”
Section: Part I: New Progress In Rna-binding/translation Suppression mentioning
confidence: 99%